2021
DOI: 10.3390/su13158165
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of a Pilot-Scale Concerning Ex-Situ Bioremediation of Petroleum Hydrocarbons Contaminated Soils

Abstract: The soil samples were taken from the site of a former oil products depot from an industrial area (Romania). The soil samples taken were analyzed from a physical and chemical point of view: texture, pH, soil micronutrient content, metals concentration and petroleum hydrocarbon concentration (PHCs). The soil contaminated with total petroleum hydrocarbon (TPH (4280 mg kg−1) was disposed in the form of a pile (L × W × H: 3000 × 1400 × 500 mm). Experiments on a pilot-scale were conducted over 12 weeks at constant p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…(2) The metal salt or metal oxide is mixed with biomass first, and then the biochar is obtained via biomass pyrolysis. Currently, the metals commonly used for biochar modification are Fe [80], Mg [68,81], and Mn [82,83]. Sun et al [42] demonstrated that Fe-modified biochar could be obtained by adding crushed rice husk to 1 M ferric chloride hexahydrate (FeCl 3 • 6H 2 O), with a mass ratio of 1:25 for Fe 3 + to biomass, and then pyrolyzed at 600 • C. Their field experiments showed that the DTPA-Cd concentration in soil, with the Fe-modified biochar treatment, decreased by 37.74-41.65% compared with that in the control group.…”
Section: Metal Salt Modificationmentioning
confidence: 99%
See 3 more Smart Citations
“…(2) The metal salt or metal oxide is mixed with biomass first, and then the biochar is obtained via biomass pyrolysis. Currently, the metals commonly used for biochar modification are Fe [80], Mg [68,81], and Mn [82,83]. Sun et al [42] demonstrated that Fe-modified biochar could be obtained by adding crushed rice husk to 1 M ferric chloride hexahydrate (FeCl 3 • 6H 2 O), with a mass ratio of 1:25 for Fe 3 + to biomass, and then pyrolyzed at 600 • C. Their field experiments showed that the DTPA-Cd concentration in soil, with the Fe-modified biochar treatment, decreased by 37.74-41.65% compared with that in the control group.…”
Section: Metal Salt Modificationmentioning
confidence: 99%
“…Their preparation methods could change greatly with the different research materials. For example, Wang et al [83] and others prepared co-existing TiO 2 nanoparticles magnetically modified kaolin by in-situ precision. Mi et al [81] prepared La-modified magnetic composite by co-precipitation.…”
Section: Mofsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies indicated that the xenobiotics biodegradation and metabolism might include the decomposition of plastic polymers and pollutants (e.g., bisphenol, toluene, benzoate, heavy metals and PAHs) [52,53,82,83]. The increase in this metabolic pathway indicated that bacteria in treated soils could use PE or PHE as a carbon source to grow/reproduce and degrade them.…”
Section: Predictive Metabolic Pathways Using Keggmentioning
confidence: 99%